2019
DOI: 10.2217/nnm-2018-0515
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Nanoceria in Imiquimod Induced Psoriasis by Inhibiting The Inflammatory Responses

Abstract: Aim: To investigate the effect of cerium oxide nanoparticles (nanoceria) on psoriasis. Materials & methods: Fourier transform infrared, powder x-ray diffraction and scanning electron microscopy were used to characterize nanoceria. Imiquimod (62.5 mg/mice) was used for the induction of psoriasis while nanoceria was administered/applied via multiple routes (topical gel, intraperitoneal and subcutaneous) as a therapeutic intervention once daily. Results: Nanoceria significantly attenuated splenic hypertrophy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…Furthermore, Eitan et al demonstrated that combination of lenalidomide and nanoceria reduce demyelination and neurological symptoms in EAE mice model by suppressing oxidative stress and inflammation [86]. In the same way, it was demonstrated that nanoceria presents an antipsoriatic effect by down regulation of inflammatory proteins (NF-κB, COX-2 and GSK3) and inhibiting Th-cell mediated IL-17/IL-23 [87].…”
Section: Cerium Oxide Nanoparticlesmentioning
confidence: 96%
“…Furthermore, Eitan et al demonstrated that combination of lenalidomide and nanoceria reduce demyelination and neurological symptoms in EAE mice model by suppressing oxidative stress and inflammation [86]. In the same way, it was demonstrated that nanoceria presents an antipsoriatic effect by down regulation of inflammatory proteins (NF-κB, COX-2 and GSK3) and inhibiting Th-cell mediated IL-17/IL-23 [87].…”
Section: Cerium Oxide Nanoparticlesmentioning
confidence: 96%
“…Whether local MN-mediated drug delivery could alleviate systemic inflammation is an important issue. Therefore, we compared the degree of splenomegaly in different groups by measuring the spleen index, which was defined by the ratio of spleen weight to body weight. , The MTX/EGCG-HP group had the lowest spleen index among all treatment groups, which was very close to the normal group (Figure S25). In addition, the percentage of immune cells in the spleen was assessed by flow cytometric analysis (Figure i).…”
Section: Resultsmentioning
confidence: 92%
“…explored to analyze the effect of 88 nm‐sized ceria nanoparticles on psoriasis mouse model induced by imiquimod (IMQ) using three different methods of administration: topical route by mixing ceria nanoparticles with carbopol gels, intraperitoneal route, and subcutaneous route. [ 80 ] Although the size of ceria nanoparticles was larger than ceria nanoparticles used in other studies, the groups treated with ceria nanoparticles, regardless of the administration route, resulted in improved outcomes. The splenomegaly was reduced in groups treated with ceria nanoparticles, and psoriasis area severity index (PASI) scoring was also reduced in terms of thickness, redness, and scaling parameters.…”
Section: Biomedical Applicationsmentioning
confidence: 98%